Correction: Evaluation of nitazoxanide treatment following triclabendazole failure in an outbreak of human fascioliasis in Upper Egypt. - Haidi Karam-Allah Ramadan; Waleed Attia Hassan; Nahed Ahmed Elossily; Alzahraa Abdelraouf Ahmad; Adnan Ahmed Mohamed; Alaa Soliman Abd-Elkader; Eman M Nagiub Abdelsalam; Hani M J Khojah (Public Library of Science (PLoS), 2020)
[This corrects the article DOI: 10.1371/journal.pntd.0007779.].